2014
DOI: 10.1073/pnas.1417351111
|View full text |Cite
|
Sign up to set email alerts
|

Label-free electrochemical detection of human methyltransferase from tumors

Abstract: The role of abnormal DNA methyltransferase activity in the development and progression of cancer is an essential and rapidly growing area of research, both for improved diagnosis and treatment. However, current technologies for the assessment of methyltransferase activity, particularly from crude tumor samples, limit this work because they rely on radioactivity or fluorescence and require bulky instrumentation. Here, we report an electrochemical platform that overcomes these limitations for the label-free dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
91
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 34 publications
1
91
0
1
Order By: Relevance
“…About four different categories of this enzyme were identified in mammals namely DNMT1, DNMT2, DNMT3A, and DNMT3B. 2,7,11,18 It was suggested that SNPs in the genes responsible for the expression of these enzymes perhaps affect their role in methylation of mutant genes. Consequently, the role of mutant genes in the pathogenesis of cancer may be altered.…”
Section: Epigenetics and Sources Methyl Groupmentioning
confidence: 99%
See 4 more Smart Citations
“…About four different categories of this enzyme were identified in mammals namely DNMT1, DNMT2, DNMT3A, and DNMT3B. 2,7,11,18 It was suggested that SNPs in the genes responsible for the expression of these enzymes perhaps affect their role in methylation of mutant genes. Consequently, the role of mutant genes in the pathogenesis of cancer may be altered.…”
Section: Epigenetics and Sources Methyl Groupmentioning
confidence: 99%
“…Consequently, the role of mutant genes in the pathogenesis of cancer may be altered. 2,11,13,18,21 In other words, genetic polymorphism of DNMT enzymes may affect their role in epigenetic modifications via gene methylation. Therefore, genetic polymorphisms and epigenetic variations may contribute simultaneously to the aetiology of cancer.…”
Section: Epigenetics and Sources Methyl Groupmentioning
confidence: 99%
See 3 more Smart Citations